ANALISIS URAIAN TUGAS TENAGA ADMINISTRASI SEKOLAH BIDANG HUBUNGAN MASYARAKAT (HUMAS) DI SLTA SE-KABUPATEN PESISIR SELATAN - Widia Salsadila; Rusdinal Rusdinal; Nellitawati Nellitawati; Novriyanti Achyar (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the job descriptions of school administrative staff in the field of public relations (PR) in senior high schools throughout Pesisir Selatan Regency. Method: This study uses a quantitative approach with a descriptive method. The sample in this study amounted to 44 respondents selected using a simple random sampling technique. Data were collected through a questionnaire with the provision of answers using a rating scale in the form of a semantic differential scale that has met the validity and reliability tests, then analyzed using the average value (mean) and Respondent Achievement Level (TCR). Results: The research results indicate that the job descriptions of school public relations administrative staff are in the good category, with an average score of 4.43 and a TCR of 87.4%. This job description consists of four indicators: the clarity of task details scored an average score of 4.38 with a TCR of 87.6%. The appropriateness of authority limits scored an average score of 4.37 with a TCR of 87.4%. The standardization of procedures (SOP) scored an average score of 4.30 with a TCR of 86%. Finally, the availability of job descriptions scored an average score of 4.41 with a TCR of 88.2%. Novelty: This study specifically provides an overview of the analysis of job descriptions of school public relations administrative staff in high schools throughout Pesisir Selatan Regency based on four indicators: clarity of task details, appropriateness of authority limits, standardization of procedures, and availability of job descriptions. It is hoped that this can serve as a document for improving job descriptions for schools.